INCREASING PERSUASION: ISLAMIC BOARDING SCHOOL PUBLIC RELATIONS THROUGH THE LIKELIHOOD ELABORATION MODEL - Hasanah, Rizkiyah (Managere: Indonesian Journal of Educational Management, 2024)
Study this aims to analyze the increased persuasion in public relations at the cottage boarding school through the elaboration likelihood model. Study This uses a qualitative case study approach. The subject study consists of the Caretaker, the Head of the Islamic Boarding School, the Islamic Boarding School Public Relations, the Management of Islamic Boarding Schools, Santri, the Guardians of Santri, and the Community. Data collection techniques include observation interviews and documentation. Data analysis techniques using data reduction, data presentation, and withdrawal conclusion. Research results show that the implementation of the ELM model in Pondok The Nurul Jadid Islamic Boarding School successfully increased the effectiveness of public relations communications. With emphasis on the path central, public relations lodge boarding school develop more substantive messages and is relevant for the audience, which engages argument logical and supporting data. This matter facilitates more understanding​ , depth, and strong commitment from the recipient's message to the message conveyed. On the other hand, the usage of the peripheral track is also important in increasing persuasion, especially in building a connection with the audience. Cottage Public Relations boarding school utilizes charismatic figures and symbols to strengthen the message conveyed.​ The existence of respected kyai and ustadz becomes an important factor in influencing the perception and response of the audience.